Radar‐Sounding Characterization of the Subglacial Groundwater Table Beneath Hiawatha Glacier, Greenland. Issue 10 (20th May 2021) - Bessette, Jonathan T.; Schroeder, Dustin M.; Jordan, Thomas M.; MacGregor, Joseph A.
Abstract: Radar‐sounding surveys associated with the discovery of a large impact crater beneath Hiawatha Glacier, Greenland, revealed bright, flat subglacial reflections hypothesized to originate from a subglacial groundwater table. We test this hypothesis using radiometric and hydrologic analysis of those radar data. The dielectric loss between the reflection from the top of the basal layer and subglacial reflection and their reflectivity difference represent dual constraints upon the complex permittivity of the basal material. Either ice‐cemented debris or fractured, well‐drained bedrock explain the basal layer's radiometric properties. The subglacial reflector's geometry is parallel to isopotential hydraulic head contours, located 7.5–15.3 m below the interface, and 11 ± 7 dB brighter than the ice–basal layer reflection. We conclude that this subglacial reflection is a groundwater table and that its detection was enabled by the wide bandwidth of the radar system and unusual geologic setting, suggesting a path for future direct radar detection of subglacial groundwater elsewhere. Plain Language Summary: Recent radar sounding of the Hiawatha Glacier, which overlies a large impact crater, also found an unusually flat, bright surface about 10 meters beneath the bottom of the ice. This surface was suspected to be the groundwater table, which has never been directly detected by radar beneath an ice sheet, but was not studied in detail. We used two three‐layer geologic models to test this hypothesis using the strength of the radar returns. We found that the layer between the ice bottom and this lower surface is likely either debris‐laden ice or fractured, well‐drained bedrock. This surface's shape and brightness are also consistent with a groundwater table and follow expected patterns of water pressure. Our results confirm the detection of a groundwater table beneath Hiawatha Glacier and show the potential for future radar surveys to further probe subglacial groundwater systems. Key Points: Radiometric and hydrologic analysis of radar‐sounding data is consistent with a reflection from a subglacial groundwater table Dual radiometric constraints indicate a layer of either debris‐laden ice or fractured bedrock above the subglacial groundwater table This first detection of a subglacial groundwater table was enabled by favorable local geology, thin ice and the wide bandwidth radar system